2012
DOI: 10.1093/jnci/djs320
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological and Molecular Study of the Relationship Between Smoking, Risk of Nasopharyngeal Carcinoma, and Epstein–Barr Virus Activation

et al.

Abstract: Smoking is not only associated with NPC risk in individuals from China but is also associated with EBV seropositivity in healthy males and is involved in EBV activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
207
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(228 citation statements)
references
References 73 publications
14
207
6
1
Order By: Relevance
“…Salted fish, suspected to contain carcinogenic nitrosamines, was shown experimentally to produce NPC in rodents (51). Recent studies also confirmed that both cigarette smoking and elevated levels of the VCA (viral capsid antigen)-IgA antibody were associated with NPC risk and that smoking appeared to activate EBV (52). Exposure to traditional herbal medicines, fumes, smoke, wood dust and burning incense has also been suggested as risk factors (47).…”
Section: Field and Laboratory Studies On Nasopharyngeal Carcinomamentioning
confidence: 92%
“…Salted fish, suspected to contain carcinogenic nitrosamines, was shown experimentally to produce NPC in rodents (51). Recent studies also confirmed that both cigarette smoking and elevated levels of the VCA (viral capsid antigen)-IgA antibody were associated with NPC risk and that smoking appeared to activate EBV (52). Exposure to traditional herbal medicines, fumes, smoke, wood dust and burning incense has also been suggested as risk factors (47).…”
Section: Field and Laboratory Studies On Nasopharyngeal Carcinomamentioning
confidence: 92%
“…The etiology of this disease involves a complex interaction of genetic factors, viral infection, and environmental factors including diet; of which, the environmental factors appear to have a relatively minor role contributing to the promotion of the disease (35). Diet, habits of smoking and/or alcohol consumption, and lifestyle contribute to the disease in the high-incidence races and each of these factors has gained experimental supports (6,7,12,(25)(26)(27)(28)(29).…”
Section: Dietary Factors Lifestyle and Environment Contribute To Thementioning
confidence: 99%
“…This suggests that internal genetic factors are the main players for the generation of the disease in these low-incidence populations. But in high-incidence regions, certain dietary materials and lifestyle add to the internal genetic factors, making the entire population much more susceptible to the disease (4,7,8,10,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Children who were fed on saltpreserved fish and other foods starting at the time of weaning are more prone to get the disease at a younger age, generally within 14-19 years.…”
Section: Environmental Inhalantsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 What triggers the reactivation, however, is less welldefined, although cigarette smoking is among the possible reactivating factors. 16,17 On the other hand, human papillomavirus (HPV), a common aetiological agent causing cervical cancer, is associated with the non-endemic, keratinising type of NPC, although evidence is limited due to its low prevalence. 18 While EBV and HPV infections are nearly always mutually exclusive in the pathogenesis of NPC, 9 studies have suggested that HPV-positive NPC is associated with poorer outcome when compared with EBV-positive NPC.…”
Section: Viral Factorsmentioning
confidence: 99%